Effect of tacticity on the phase behavior and demixing of p alpha MSAN/dPMMA blends investigated by SANS - Aoki,Y; Sharratt,W; Wang,H; O'Connell,R; Pellegrino,L; Rogers,S; Dalgliesh,RM; Higgins,JS; Cabral,JT (Macromolecules, 2020)
We investigate the effect of polymer tacticity on the phase behavior and phase separation of polymer mixtures by small-angle neutron scattering (SANS). Poly(α-methyl styrene-co-acrylonitrile) (PαMSAN) and deuterated poly(methyl methacrylate) (dPMMA) with two degrees of syndiotacticity were selected as a model partially miscible blend, as one of the most highly interacting systems known (defined by the temperature dependence of the blend’s interaction parameter). One-phase (equilibrium) and time-resolved, spinodal demixing experiments were analyzed by de Gennes’ random phase approximation (RPA) and Cahn–Hilliard–Cook (CHC) theory, respectively. The second derivative of the Gibbs free energy of mixing with respect to composition (G″ ≡ ∂2ΔGm/∂2) and corresponding χ parameter were obtained from both RPA and CHC analysis and found to correlate well across the phase boundary. We find that blends with higher PMMA syndiotacticity exhibit greater miscibility and a steeper G″ temperature dependence by ∼40%. The segment length of dPMMA with higher syndiotacticity was found to be a = 7.4 Å, slightly larger than 6.9 Å reported for lower syndiotacticity dPMMA. Consideration of thermal fluctuations is required for the self-consistent analysis of the nontrivial evolution of the spinodal peak position q over time, corroborated by CHC model calculations. The temperature dependence of the mobility parameter, M, can be described by a “fast-mode” average of the diffusion coefficients of the blend constituents, except for quenches originating near the glass transition. A minimum demixing length scale of Λ ≈ 40 nm is obtained, in agreement with the theory for deeper quenches, but deviates at shallower quenches, whose origin we discuss. CHC correctly describes demixing length and time scales, except for quenches into the vicinity of the spinodal boundary. Our data demonstrat